2017
DOI: 10.1128/jvi.01389-16
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylphosphatidylinositol-Anchored Anti-HIV scFv Efficiently Protects CD4 T Cells from HIV-1 Infection and Deletion in hu-PBL Mice

Abstract: Despite success in viral inhibition and CD4 T cell recovery by highly active antiretroviral treatment (HAART), HIV-1 is still not curable due to the persistence of the HIV-1 reservoir during treatment. One patient with acute myeloid leukemia who received allogeneic hematopoietic stem cell transplantation from a homozygous CCR5 Δ32 donor has had no detectable viremia for 9 years after HAART cessation. This case has inspired a field of HIV-1 cure research focusing on engineering HIV-1 resistance in permissive ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…Expression of GPI-scFvs after cotransfection into 293T cells. Our past studies with CD4 ϩ cells stably expressing GPI-scFvs from integrated lentiviral vectors demonstrated potent blocking of HIV-1 entry (28,35). In order to bypass viral entry and examine the effect of anti-HIV Env GPI-scFvs on later stages of the viral replication cycle, we cloned the GPI-scFv fusion genes into the plasmid expression vector pcDNA3, which was then cotransfected with HIV-1 proviruses into 293T cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of GPI-scFvs after cotransfection into 293T cells. Our past studies with CD4 ϩ cells stably expressing GPI-scFvs from integrated lentiviral vectors demonstrated potent blocking of HIV-1 entry (28,35). In order to bypass viral entry and examine the effect of anti-HIV Env GPI-scFvs on later stages of the viral replication cycle, we cloned the GPI-scFv fusion genes into the plasmid expression vector pcDNA3, which was then cotransfected with HIV-1 proviruses into 293T cells.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, our study demonstrates the potential of the anti-HIV Env GPI-scFvs as unique antiviral molecules which derive potent inhibitory activity against HIV-1 replication by interfering with both early (receptor binding) and late (Env processing and incorporation into virions) stages of the viral life cycle. A recent study by Ye et al in SCID-PBL mice infected with HIV demonstrated greater persistence of GPI-X5-modified CD4 ϩ T cells, further suggesting the potential use of anti-HIV Env GPI-scFvs as a genetic intervention to protect CD4 ϩ T cells from infection (35). It may also be important to extend these studies to an immunocompetent host infection model such as the simian-human immunodeficiency virus (SHIV)-rhesus macaque model in order to evaluate the capacity of anti-HIV Env GPI-scFv to protect permissive cells and restore immunological control of the infection.…”
Section: Discussionmentioning
confidence: 97%
“…Because many cell surface proteins are naturally expressed on the plasma membrane by covalently attaching a GPI anchor (72, 73), we think that a GPI scaffold might be a safer one than other membrane-anchored scaffolds, especially for linking a small peptide; the GPI attachment signal of decay-accelerating factor (DAF) efficiently anchors the antiviral peptides in the lipid rafts of the plasma membrane, which can result in a locally high peptide concentration to maximize antiviral activity (42,43). By using the GPI scaffold, Zhou and coworkers successfully anchored HIV-1-neutralizing antibodies on the lipid rafts of the transduced target cells, conferring high-level resistance to HIV-1 infection (33,(74)(75)(76)(77). It was found that GPI-anchored scFv X5 efficiently protected CD4 ϩ T cells from HIV-1 infection and deletion in humanized mice (76).…”
Section: Discussionmentioning
confidence: 99%
“…[99][100][101] Consequently, it contributes to long-term persistence against HIV-1 infection in vitro and in vivo and provides CD4 + T helper signals to boost anti-HIV CAR CD8 + T cell function. 102,103 Finally, the distance between the target cell and CAR cell, which vary depending on the size of the antigen and localization of its epitope recognized by scFv-CAR T is thought to play a key role in the activation of CAR-T cells. For instance, in leukemia, scFv CAR-T cells that target membrane-proximal epitope on CD22 possess higher anti-F I G U R E 4 Schematic presentation of anti-HIV bi-, tri-and multiple specific CAR.…”
Section: Hiv Therapy Using Cd4-based Car T Cellsmentioning
confidence: 99%